Multi-step parallel synthesis enabled optimization of benzofuran derivatives as pan-genotypic non-nucleoside inhibitors of HCV NS5B. Issue 7 (1st April 2020) - Xiao, Dong; Dai, Xing; Liu, Hong; He, Shuwen; Shi, Zhi-Cai; Ludmerer, Steven W.; Li, Fangbiao; Nargund, Ravi; Palani, Anandan
Graphical abstract: Abstract: In a lead optimization effort towards NS5B NNI inhibitors, two multi-step parallel libraries were designed and successfully synthesized. Through this effort we discovered compound 9B, which achieved rigorous and delicate balance of inhibition across the common genotypes and mutants with <10 nM potency. In addition, the bicyclic compounds 9B exhibited improved FASSIF solubility over the tetracyclic compound MK-8876. This strategic approach demonstrated that, even within limited reaction scope, multi-step parallel libraries could provide access to more complex chemical space. This expedient access facilitates diverse, purpose-driven optimization of SAR and physicochemical properties.